'Cumulative Deterrence' as a New Paradigm for Cyber Deterrence. Issue 1 (2nd January 2017) - Tor, Uri
ABSTRACT: This article suggests that there is a paradigm crisis in the sub-field of cyber deterrence. Cyber deterrence is evolving slowly and unpromisingly as a strategic tool in both theory and practice, mostly due to the ill-fitting theoretical framework and underlining assumptions it borrows from the absolute-nuclear-deterrence context. Therefore, this article suggests replacing the accepted yet inadequate paradigm of absolute deterrence with a better-fitting restrictive-cumulative-deterrence paradigm that draws on the Israeli approach to deterrence, introducing it into the cyber domain. The article further criticizes the current discourse in the field, including some 'common knowledge' (mis)understandings of cyberspace and the ways it affects the possibility of deterrence.